Risco de Farmingham e evento cardiovascular em mulheres com síndrome dos ovários policísticos - Santos, Ana Gabriela Pontes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: Women with polycystic ovary syndrome (PCOS) have an increased prevalence of cardiovascular risk factors. However, most studies available are limited to confirming the association of PCOS with cardiovascular morbidity and mortality. Objectives: To assess the Framingham risk score and the prevalence of cardiovascular events in women with PCOS. Patients and Methods: Clinical, biochemical and ultrasonographic data were collected from women (18-40 years) with and without PCOS attending the Botucatu Medical School Hospital from 1997 to 2010. The Framingham Risk Score (FRS), calculated according to NCEP-ATPIII-2002 criteria, was used to estimate the 10-year risk of first coronary event. The prevalence of major and minor cardiovascular events was obtained through the analysis of medical records, crossing of data, and active search. Statistical analyses were performed using the Chi-square test, Fischer’s exact test and multiple logistic regression adjusted for age and BMI, with significance set at 5%. Results:t A total of 267 women with PCOS and 190 without PCOS were followed up for 1-13 years. Median age was 25 years in women with PCOS, and 29.5 yearsnin those without it (p<0.0001). Women with PCOS had higher prevalence of obesity (p=0.017), waist circumference (p= 0.012), arterial hypertension (p=0.047), glucose intolerance (p=0.027), type 2 diabetes mellitus (p=0.007 hypercholesterolemia (p=0.005), and hypertriglyceridemia (0.002) than those without PCOS. The prevalence of high FRS was 7.5% and 1.3% in women with and without PCOS, respectively (p=0.008). Multiple logistic regression analysis revealed that women with PCOS had a 5-fold greater chance of having a coronary event than those without PCOS (OR: 5.16 95%CI:1.16-22.96, p=0.031). However, the prevalence of cardiovascular events did not statistically differ between women with and without PCOS. Conclusions: In the women with PCOS at childbearing age who participated in this ...

Introdução Mulheres com Síndrome dos Ovários Policísticos (SOP) apresentam prevalência aumentada de fatores de risco cardiovascular. Entretanto, os estudos que confirmam a associação entre SOP e a morbimortalidade por doença cardiovascular são limitados. Objetivos Avaliar o risco de Framingham a prevalência de evento cardiovascular em mulheres com SOP. Pacientes e Método Foram analisados os dados clínicos, bioquímicos e ultrassonográficos de mulheres com idade entre 18-40 anos com e sem diagnóstico de SOP, do HC-FMB no período de 1997 a 2010. Para verificar o risco de primeiro evento coronariano em dez anos, foi utilizado o escore de risco de Framingham (ERF), modificado pelo NCEP-ATPIII, 2002. A prevalência de evento cardiovascular maior e menor foi obtida pela análise dos prontuários médicos, cruzamento de dados e busca ativa. O teste do qui-quadrado, o teste exato de Fisher e análises de regressão logística multivariada corrigidas para idade e índice de massa corporal (IMC), foram empregados nas análises estatísticas e o nível de significância considerado foi de 5%. Resultados Foram identificadas 267 mulheres com SOP e 190 sem SOP seguidas no período de um a 13 anos. A mediana de idade foi de 25 anos (SOP) e de 29,5 (não SOP) (p<0,0001). As pacientes com SOP apresentaram maior prevalência de obesidade (p=0,017), circunferência da cintura (p= 0,012), hipertensão arterial sistêmica (p=0,047), intolerância à glicose (p=0,027), Diabetes mellitus do tipo 2 (p=0,007), hipercolesterolemia (p=0,005) e hipertrigliceridemia (0,002) em relação às não SOP. As pacientes com SOP apresentaram uma prevalência de 7,5% de ERF alto contra 1,3% nas não SOP (p=0,008), e a análise de regressão logística multivariada mostrou uma chance cinco vezes maior de evento coronariano quando se comparou às não SOP (OR 5,16 IC95%:1,16-22,96;p=0,031). Entretanto, não houve diferença estatística entre a prevalência de eventos ...
Framingham risk cardiovascular event in women with polycystic ovary syndrome
Keywords: Stein-Leventhal, Sindrome de; Sistema cardiovascular - Avaliação de riscos se saúde; Coração - Doenças; Ovarios - Tumores; Cardiovascular system Diseases